Morocco : Staff Report for the 2003 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This 2003 Article IV Consultation highlights that Morocco's growth performance over the last decade has not been strong enough to reduce poverty. Growth has also been volatile because of the impact of recurrent drought conditions on agricultural output. Economic conditions improved in 2002 despite a less favorable international environment, which was marked by a decline in tourism and external demand. Real GDP growth reached 4.5 percent reflecting a further rise in agricultural output and somewhat higher growth in the nonagricultural sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet